POLITICAL REPRESENTATION OF WOMEN IN THE BANGKA TENGAH DITRICT LEGISLATURE REGENCY FOR THE 2019-2024 PERIOD - Ferdian, Dirga (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
This research discusses the political representation of women in the Central Bangka Regency legislature. The substantial presence of women in the legislature is very important, not just to complete the seats but as an effort to provide access and authority to women to be able to carry their interests. Political representation does not discuss how many representatives are present in a parliament, but looks at how the process of represented interests can be carried by those who represent them. The presence of women as a council is expected to bring the interests of women, through their role in shaping policies in the fulfillment of fair rights for women. The purpose of this research is to find out the political representation of women and also the obstacles faced by women council members in the legislative body of the Regional People's Representative Council of Bangka Tengah Regency for the 2019-2024 period. The theory used in this research is Hanna Fenichel Pitkin's theory of Representation. The research method in this study is using Qualitative research methods with data collection techniques of observation, interviews, and documentation as supporting data. The results of this study are the political representation of women in the Bangka Tengah Regional House of Representatives based on formal representation, there are 4 female councilors, then descriptive representation is characterized by similarities in gender characteristics and interests, and symbolic representation is seen from the similarity between the identities that represent. Meanwhile, in substantive representation based on the legislative function, the BangkaTengah Regional House of Representatives can be said to be good. This is because there are 4 local regulations agreed upon relating to women and children. The budget function of the council's substantive representation runs very well, this is shown by the increase in the budget every year at DP2KBP3A. The supervisory function based on substantive representation can be said to be good, this is because Central Bangka Regency managed to get the Parahita Ekapraya Award. In addition, there are no significant obstacles faced by women councils in the Central Bangka Regional House of Representatives. This is because they have been on the council for a long time and have the experience to deal with all situations.